Detection of fructophilic lactic acid bacteria (FLAB) in bee bread and bee pollen samples and determination of their functional roles - Ispirli, Humeyra; Dertli, Enes (WILEY, 2021)
In this study, bee bread and bee pollen samples were characterized in terms of presence of fructophilic lactic acid bacteria (FLAB). Following discrimination and identification of FLAB strains, their functional roles were determined. Genotypic characterization of FLAB strains revealed the presence of 27 distinct strains belonging to Lactobacillus kunkeei (21), Fructobacillus fructosus (3), Lactobacillus plantarum (2), and Leuconostoc mesenteroides (1) strains. In terms of functional roles, all FLAB strains demonstrated high levels of autoaggregation and hydrophobicity properties whereas L. kunkeei and F. fructosus strains did not tolerate bile salts and low pH conditions. A low level of antibiotic resistance was observed among FLAB strains and importantly FLAB strains demonstrated high levels of antibacterial and antifungal activities where strain specific properties played roles. The highest exopolysaccharide (EPS) production yields were obtained for L. kunkeei AP15, AP37 and L. mesenteroides AP-40 which produced 2.79, 2.01, and 5.37 g/L EPS, respectively. Practical applications Bee bread and bee pollen are among beneficial bee products produced and consumed in all over the world. Production of bee bread relies on the fermentation process of bee pollen where a special LAB group FLAB plays roles. Despite the increment of the importance of these products for human consumption, there is a lack of knowledge for the microbial composition of these products. In this study, FLAB strains were isolated and identified from bee bread and bee pollen samples, and their technofunctional role was determined. The FLAB strains would be evaluated as starter cultures for production of bee products under industrial conditions.
Keywords: LACTOBACILLUS; RESISTANCE; SOURDOUGH; ADHESION; DEXTRAN; Food Science & Technology